HACIA UN ESTUDIO MARXIANO DEL INTERNET - Fuchs, Christian (2017)
Within the systemic crisis experienced by capitalism and the new emergence of Karl Marx, it is relevant to understand the importance of the Internet in capitalism as both domination and exploitation, as well as its potential of liberation. The article approaches the approaches of Critical Internet Studies such as Critical Studies of Cyberculture and Critical Studies of both Political Economy and Critical Theory of the Internet,seeking to focus from the different approaches to Critical Internet Studies, the role Contemporary that the Internet has in capitalism and the importance of Marx for its analysis through eleven concepts: dialectic, capitalism, commodification, surplus value/ exploitation/alienation/class, globalization, ideology, class struggle, common, public sphere, communism and aesthetics.